Synopsis: An assessment of the livestock economy in mixed crop-livestock production systems in Ethiopia - Negassa, Asfaw; Bachewe, Fantu Nisrane; Taffesse, Alemayehu Seyoum; Dereje, Mekdim (International Food Policy Research Institute, 2017)
The livestock sub-sector has contributed little to the remarkable economic growth recorded in Ethiopia in the last decade. In an effort to stimulate livestock production, the Ethiopian government has recently recognized livestock as an important strategic sub-sector in which to invest. Unlike most studies that focus purely on aspects of livestock production, this study provides a detailed descriptive assessment of the livestock production and marketing behavior of smallholder mixed crop-livestock farmers.